Addressing mood and fatigue in return-to-work programmes after stroke: a systematic review - Chen, Nicole Yun Ching; Dong, YanHong; Kua, Zaylea Zhong Jie (Frontiers in Neurology, 2023)
Introduction Return-to-work is a key rehabilitation goal for many working aged stroke survivors, promoting an overall improvement of quality of life, social integration, and emotional wellbeing. Conversely, the failure to return-to-work contributes to a loss of identity, lowered self-esteem, social isolation, poorer quality of life and health outcomes. Return-to-work programmes have largely focused on physical and vocational rehabilitation, while neglecting to include mood and fatigue management. This is despite the knowledge that stroke results in changes in physical, cognitive, and emotional functioning, which all impact one’s ability to return to work. The purpose of this systematic review is to conduct a comprehensive and up-to-date search of randomised controlled trials (RCTs) of return-to-work programmes after stroke. The focus is especially on examining components of mood and fatigue if they were included, and to also report on the screening tools used to measure mood and fatigue. Method Searches were performed using 7 electronic databases for RCTs published in English from inception to 4 January 2023. A narrative synthesis of intervention design and outcomes was provided. Results The search yielded 5 RCTs that satisfied the selection criteria (n = 626). Three studies included components of mood and fatigue management in the intervention, of which 2 studies found a higher percentage of subjects in the intervention group returning to work compared to those in the control group. The remaining 2 studies which did not include components of mood and fatigue management did not find any significant differences in return-to-work rates between the intervention and control groups. Screening tools to assess mood or fatigue were included in 3 studies. Conclusion Overall, the findings demonstrated that mood and fatigue are poorly addressed in rehabilitation programmes aimed at improving return-to-work after stroke, despite being a significant predictor of return-to-work. There is limited and inconsistent use of mood and fatigue screening tools. The findings were generally able to provide guidance and recommendations in the development of a stroke rehabilitation programme for return-to-work, highlighting the need to include components addressing and measuring psychological support and fatigue management.